Superconductivity in interacting interfaces of cuprate-based heterostructures. (6th June 2018) - Di Castro, Daniele; Balestrino, Giuseppe
Abstract: Low dimensional superconducting systems have been the subject of numerous studies in the recent past, with the aim of achieving a higher and higher critical temperature ( T c ). The recent improvement in film deposition techniques has allowed the realization of artificial heterostructures, with atomically flat surfaces and interfaces, where novel properties appear that are not present in the single constituent. For instance, quasi-2D superconductivity was found at the interface between different oxides. In this review we analyze, in particular, the quasi-2D superconductivity occurring at the interface between two non-superconducting oxides, mostly cuprates. Throughout a comparison of the superconducting properties of different oxide heterostructures and superlattices, we propose a phenomenological explanation of the behavior of the T c as a function of the number of conducting CuO2 planes. This is achieved by introducing two different interactions between the superconducting 2D sheets. This interpretation is finally extended also to standard high T c cuprates, contributing to the solution of the long-standing question of the dependence of T c on the number of CuO2 planes in these systems.